(untitled) (Journal of the College of Basic Education, 2022)
Universities are the appropriate environment for achieving the progress of nations in various fields of civilization.Being the environment through which qualified and morally and psychologically trained cadres and brains are preparedsocially, scientifically, mentally and practically in various sciences to meet the needs and requirements of the labor market,Universities work to develop and develop their societies, create their present and always planfor its prosperous future. These universities are viewed as educational human societies in which different species are activeOf the interactions and relationships between the various members of this community, which aims finally to provideStudents provide information, knowledge, experiences, skills, attitudes and values ​​that contribute to building a personalityThe individual in all its aspects, to be a "good" citizen who is affected and influenced by his society and works on